SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN TINGKAT KEPUASAN PELANGGAN TERHADAP PELAYANAN PADA CAFE ALGO MAKASSAR - Supriadi; Kurnia Yahya; Samsuriah (P3M STMIK Profesional Makassar, 2022)
Decision Support Systems can be defined as information systems and analytical models designed to determine decision makers to get better information. By utilizing this SPK, it is believed that it will really help dynamics in overcoming problems to determine the level of customer satisfaction with Cafe Algo services. The SPK method in this study uses SAW, this method is used to determine the weight of the criteria for attributes, in the positioning system. it will create the best option with absolutely precise calculations. The alternative is customers assessing service quality based on predetermined standards. The final result of this calculation concludes that in general, the average customer is satisfied with the service quality of Cafe Algo.